Improving Speaking Ability Through Community Language Learning of The Eleventh Grade Students at SMK Negeri 5 Medan - Marlina Hutabarat (The Explora, 2020)
This study is intended to find out whether Community Language Learning can improve significantly students’ speaking ability. Community Language Learning is very important in teaching learning process because they give students an opportunity to practice communicating in different social context in different social rules, Community Language Learning can be set up so that they are very structured or in a less structured way. This study is conducted by using Class Action Research. The subject of this study was the second grade students of SMK Negeri 5 Medan. The sample of the study is the students XI-TPM1 consisting 30 students. These following suggestions are directed for the students of English Department, it is suggested to know or learn kinds of method so they are easier to express their ideas and for the teachers, it would be better using some of the method and asked the students to make a conversation based on the time sequence. The teacher is suggested to make variation technique for students to improve students’ speaking ability and, so the students interested inthe speaking English.